Party members and high-intensity participation: evidence from Brazil - Floriano Ribeiro, Pedro; Do Amaral, Oswaldo E. (Revista de Ciencia Política, 2020)
The literature on political parties has indicated a decline in the levels of party membership in established democracies. The few studies on Latin America show impressive membership figures, but they say nothing about profile and motivations of these individuals. Relying on original data from the first survey undertaken exclusively with party members in Brazil, this article describes the activists’ profiles and explains the determinants of high-intensity participation. The findings show that activists are older, have a higher socioeconomic status, and present positive attitudes about participation. The multivariate analysis indicates that high-intensity participation is anchored in collective incentives, cognitive resources, and the perception of political efficacy. Brazil’s political parties have an internal life and grassroots activities, which contradicts the traditional view of them.